Genome-Wide Transcriptional Profiling to Elucidate Key Candidates Involved in Bud Burst and Rattling Growth in a Subtropical Bamboo (Dendrocalamus hamiltonii) - Bhandawat, Abhishek; Singh, Gagandeep; Seth, Romit; Singh, Pradeep; Sharma, Ram K. (Frontiers in Plant Science, 2017)
Bamboo, one of the fastest growing plants, can be a promising model system to understand growth. The study provides an insight into the complex interplay between environmental signaling and cellular machineries governing initiation and persistence of growth in a subtropical bamboo (Dendrocalamus hamiltonii). Phenological and spatio-temporal transcriptome analysis of rhizome and shoot during the major vegetative developmental transitions of Dendrocalamus hamiltonii was performed to dissect factors governing growth. Our work signifies the role of environmental cues, predominantly rainfall, decreasing day length and high humidity for activating dormant bud to produce new shoot, possibly through complex molecular interactions among phosphatidylinositol, calcium signaling pathways, phytohormones, circadian rhythm and humidity responses. We found the coordinated regulation of auxin, cytokinin, brassinosteroid signaling and cell cycle modulators; facilitating cell proliferation, cell expansion and cell wall biogenesis supporting persistent growth of emerging shoot. Putative master regulators among these candidates were identified using predetermined Arabidopsis thaliana protein-protein interaction network. We got clues that the growth signaling begins far back in rhizome even before it emerges out as new shoot. Putative growth candidates identified in our study can serve in devising strategies to engineer bamboos and timber trees with enhanced growth and biomass potentials.